2018
DOI: 10.1016/j.stem.2018.01.008
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Labeling by CD73 Marks Multipotent Stromal Cells and Highlights Endothelial Heterogeneity in the Bone Marrow Niche

Abstract: Despite much work studying ex vivo multipotent stromal cells (MSCs), the identity and characteristics of MSCs in vivo are not well defined. Here, we generated a CD73-EGFP reporter mouse to address these questions and found EGFP MSCs in various organs. In vivo, EGFP mesenchymal cells were observed in fetal and adult bones at proliferative ossification sites, while in solid organs EGFP cells exhibited a perivascular distribution pattern. EGFP cells from the bone compartment could be clonally expanded ex vivo fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
45
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(50 citation statements)
references
References 41 publications
(49 reference statements)
5
45
0
Order By: Relevance
“…Concomitantly, cells falling into the Sca-1 int CD105 hi gate were highly enriched in expression of the sinusoidal marker Flt-4 (vascular endothelial growth factor receptor-3) 12 . In agreement with previous work and with their reported role in recruitment of circulating cells to BM, sorted SECs displayed highest levels of expression of adhesion molecules such as P-, E-selectin and VCAM-1 60 62 at messenger RNA and/or protein levels (Supplementary Fig. 3c, d ).…”
Section: Resultssupporting
confidence: 92%
“…Concomitantly, cells falling into the Sca-1 int CD105 hi gate were highly enriched in expression of the sinusoidal marker Flt-4 (vascular endothelial growth factor receptor-3) 12 . In agreement with previous work and with their reported role in recruitment of circulating cells to BM, sorted SECs displayed highest levels of expression of adhesion molecules such as P-, E-selectin and VCAM-1 60 62 at messenger RNA and/or protein levels (Supplementary Fig. 3c, d ).…”
Section: Resultssupporting
confidence: 92%
“…CD73 is a well-known surface marker for identifying mesenchymal stem cells [23]. Recent investigations revealed the potential for CD73+ photoreceptor precursors in future cell replacement therapy [39], and showed that CD73 could mark a multipotent stromal population [40]. CD73 was also reported to mark a fraction of mammary cells endowed with lineage plasticity [41].…”
Section: Discussionmentioning
confidence: 99%
“…Contrariwise, the loss of function for ECC and ECC-differentiated neuron-like cells is the diminished capacity of authentic stemness (eg, their inability to become mature neurons, defect in functional integration, etc.). Following this novel route of logical reasoning, cautions are deemed necessary when trying to use the NT2/N cells in vitro for investigating NSC and adult neuronal properties, modeling neuronal diseases, or discovering neuronal therapeutics [ 109 , 110 ]. We believe that data extrapolation without factoring the essential cell biology discrepancy could yield misleading information because changes in survival metabolic events may induce alterations of stemness marker presentations.…”
Section: Cscs Are Tumor Survival Cellsmentioning
confidence: 99%
“…To add special insight to the word “stem” when it is used to describe cancer cells for research and therapeutic development [ 110 ].…”
Section: Potential Benefits Of Adopting Tsc As a New Nomenclature To mentioning
confidence: 99%